Community upbringing and its impact on political participation in Iraq after 2003: international and political journal - Hane, Assistant Lecturer: Nadia Abdul HadiSwadi (The International and Political Journal, 2025)
Community upbringing is a major process in building the individual from birth and preparing him to integrate easily into society. This is done through means. the most important is the family. Community upbringing represents a framework that includes a set of basic values ​​and principles to guide the individual and give him an acceptable amount of attention and political. economic and social knowledge through the family. school. media. and religious and cultural institutions The family has a major role in building the individual’s personality. directing and advising him. and educational institutions also form the political awareness of individuals as well as self-control to become responsible members of society and encourage active participation in political life to preserve the political system and ensure its continuity with the aim of reaching a strong and stable democratic country All of this is done through the individual’s interaction with public life through the influence of his societal upbringing on his political awareness